2018
DOI: 10.1149/08201.0073ecst
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Zein/Bioactive Glass Layers Using Electrophoretic Deposition Technique

Abstract: Coatings of zein and zein/bioactive glass composites were produced on 316L stainless steel using anodic electrophoretic deposition (EPD). Zein and 45S5 bioactive glass were dispersed in a binary water/ethanol solution. The effects of the zein and bioactive glass concentrations as well as different water/ethanol ratios on the coating characteristics were investigated. Also, the influence of applied voltage and deposition time were analyzed. Prior to EPD, the zeta potential of zein, bioactive glass and zein/bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Subsequently, 5 g/L of 45S5 BG was added and the suspension was placed in an ultrasonication bath for 90 minutes. The optimum concentration of zein and BG concentration and suspension pH = 3 was chosen on the basis of previous studies, which has shown appropriate results for orthopedic applications 23 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, 5 g/L of 45S5 BG was added and the suspension was placed in an ultrasonication bath for 90 minutes. The optimum concentration of zein and BG concentration and suspension pH = 3 was chosen on the basis of previous studies, which has shown appropriate results for orthopedic applications 23 …”
Section: Methodsmentioning
confidence: 99%
“…The high degradation rate of Mg implant can cause premature mechanical failure of implants before the tissues completely heal and gain their mechanical strength 4 . To slow down this degradation so that it matches the healing rate of tissues, the magnesium substrates can be coated with various biocompatible materials and their combinations, for example, chitosan, 10,11 zein, 12‐14 gelatin, 15,16 hydroxyapatite (HA), 17‐19 and bioactive glasses 15,20‐24 . Much work has been done on the composite coatings, and their application can significantly promote bone growth, protect against corrosion, and increase the functionality and durability of the implants 25 …”
Section: Introductionmentioning
confidence: 99%
“…One of the promising biopolymers showing favorable properties as a coating material is zein. It is an alcohol-soluble, natural protein–polymer obtained from corn, which has gained interest in biomedical application due to its biocompatibility, biodegradability and low toxicity [ 11 , 12 ]. Zein is classified in three fractions: α (is the most abundant), β and γ differing in solubility.…”
Section: Introductionmentioning
confidence: 99%
“…The typical peak for α-zein on an FTIR spectrum occurs for signals between 1600 and 1700 cm −1 [ 10 , 14 ]. The insolubility of zein in water is related to the high content of hydrophobic residues, such as proline, leucine, alanine and phenylalanine [ 11 , 15 , 16 ]. Zein can be potentially used to deliver drugs inside the cell cytoplasm in pharmaceutical applications, to perform 3D porous zein scaffolds or to form coatings [ 10 , 11 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The second probable reason for the agglomeration of BG particles could be attributed to their low zeta potential in slightly acidic pH of pectin solutions (Moreira et al, 2014;Fabiola Munarin et al, 2014). When the zeta potential is low, the particles tend to aggregate (Doostmohammadi et al, 2011;Ramos Rivera, Dippel, & Boccaccini, 2018).…”
Section: Formation Of Pectin-bioactive Glass Composites and µCt Examimentioning
confidence: 99%